Effects of care assistant communication style on communicative behaviours of residents with dementia: a systematic multiple case study. Issue 1 (17th October 2018) - Stanyon, Miriam; Thomas, Shirley; Gordon, Adam; Griffiths, Amanda
Abstract : Objectives: To determine whether varying the communication style of care assistants, encouraging them to use direct instructions and allowing more time for residents' responses influenced the communicative behaviour of care home residents living with dementia. Design: This study used a multiple systematic case study design. Participants were video‐recorded during morning care routines in three communication conditions: usual communication, direct instructions and pacing (allowing more time for resident responses). Each dyad acted as its own control. Setting: The study took place in a residential care home in the East Midlands, UK. Participants: Three dyads (person with dementia/care worker) Measures: The level of compliance with instructions was measured. Validated measures were used to rate positive communicative behaviour (engagement with care tasks, eye contact and initiation of interaction) and negative communicative behaviour (e.g. shouting and kicking). Results: Care assistants were able to employ direct instructions after brief training. The use of direct instructions was positively correlated with positive communicative behaviour from residents (p < 0.05). The pacing condition was not employed adequately to evaluate effectiveness. Negative communicative behaviour (resistiveness to care) was rare. Conclusion: The use of direct instructions by care assistants holds promise for effective communication with people with dementia and warrants further investigation in larger samples and in varied contexts.